Coping strategies and adjustment to multiple sclerosis among recently diagnosed patients: the mediating role of sense of coherence. (October 2017) - Calandri, Emanuela; Graziano, Federica; Borghi, Martina; Bonino, Silvia
Objective: To examine the relationship between coping strategies (problem solving, emotional release, and avoidance) and adjustment (health-related quality of life, depression, and affective well-being) in a group of recently diagnosed multiple sclerosis patients (up to three years since diagnosis), and to explore the mediating role of sense of coherence between coping strategies and adjustment. Design: Cross-sectional. Setting: Multiple Sclerosis Clinic Centre. Subjects: A total of 102 patients (61.8% women; age (years): M = 35.8, SD = 11.9; 95% with a relapsing–remitting form of multiple sclerosis; Expanded Disability Status Scale score, between 1 and 4). Interventions: Not applicable. Main measures: Coping with multiple sclerosis (problem solving, emotional release, and avoidance), sense of coherence, health-related quality of life (SF-12), depression (CES-D), and affective well-being (PANAS). Results: Problem solving was linked to higher mental health ( β = 0.28) and higher affective well-being ( β = 0.36), emotional release was related to lower depression ( β = −0.22); avoidance was associated to higher mental health ( β = 0.25), higher affective well-being ( β = 0.24), and lower depression ( β = −0.29 ) (all betas were significant at p < 0.05). Sense of coherence mediated the relationship between emotional release and depression (Sobel z -value = −2.00; p < 0.05) and the relationship between avoidance and all the indicators of adjustment (mental health: Sobel z -value = 1.97; depression: Sobel z -value = −2.02; affective well-being: Sobel z -value= 2.05; p < 0.05). Conclusions: Emotional and avoidant coping strategies seem to be adaptive among recently diagnosed multiple sclerosis patients. A mediating role between coping strategies and adjustment is played by sense of coherence.